The Potential of an Inexpensive Plant-Based Medium for Halal and Vegetarian Starter Culture Preparation - Bella Tiara Ayu; Nuttaporn Chamnipa; Jirawan Apiraksakorn (Fermentation, 2023)
The restrictions for halal and vegetarian fermented products apply not only to the food ingredients, but also to the inoculum media. The utilization of a medium for lactic acid bacteria (LAB) leads to some issues from animal-derived proteins sources that may be doubtful for halal and/or vegetarian use. This study aimed to develop a plant-based medium for culturing and maintaining LAB. The result demonstrated that 10 g/L soybean powder in sweet potato extract was suitable for cultivating Lactiplantibacillus plantarum TISTR 2075 with no significant difference (p < 0.05) from MRS (de Man, Rogosa and Sharpe) in the cell number (9.12 log CFU/mL) and specific growth rate (0.04). The feasibility of a plant-based medium to grow and maintain the LAB strains from different origins was evaluated. Compared to MRS, Lpb. plantarum TISTR 2075, Lpb. plantarum MW3, and Lacticaseibacillus casei TISTR 1463 could grow almost as well in a plant-based medium. This medium was also suitable for maintaining the viability of LAB during storage, especially when subjected to slant agar stock culture. It is practical and costs at least 10 times less than MRS. Thus, this study created a low-cost plant-based medium that could be used in laboratories, especially for applications in halal and vegetarian food products.